Hubungan Karakteristik, Pengetahuan dengan Sikap Mahasiswa STIKes PHI terhadap Narkoba Tahun 2012 - Eliya Eliya; Acep Setiawan (Jurnal Persada Husada Indonesia, 2014)
Drug abuse, psychotropic and addictive substances (drugs) or popularly termed a group of drugs among our society is increasingly showing signs of concern. Adolescents as the future generationwhen it was already contaminated drugs. Recorded 19% of adolescents in Indonesia or around 14 thousand teenagers, indicated becomedrug users. The number of drug addicts in Indonesia based on a survey of BNN in 2008, as many aswas 1.99% of the population or about 3.3 million people. Based on the amount of 1.3 million addicts were ceme from the student and the university student, while twomillionpeople of the non-student. Head of the National Narcotics Agency (BNN), Gories Mere). The purpose of this study to determine the relationship characteristics of the level of knowledge student attitude STIKEes Husada Persada Indonesia on towards drugs abuse. This study using cross sectional descriptive correlationalthe research subjects were student STIKes PHI. These research proses was conducted in Jakarta in April-June 2012. Total populationwith a sample of 84 523 respondents. The method use in sampling was stratified random sampling. The results showed the majority of respondents,sex male, average age 20 years and over (66.7%), mostly from West Kalimantan (75%), and the majority religion are Catholics. There area significant relationship between knowledge and attitudes of studens STIKes PHI on drugs(p = 0.024) <0.05. In conclusion, the higher the level of knowledge about the drug, the more positive attitude towards drugs also.